O17.1 HPV focal 48 month exit results by age for women HPV or LBC negative at baseline screening. (14th July 2019) - Ogilvie, Gina; Niekerk, Dirk Van; Krajden, Mel; Smith, Laurie; Cook, Darrel; Martin, Ruth; Stuart, Gavin; Ceballos, Kathy; Lee, Marette; Peacock, Stuart; Franco, Eduardo; Coldman, Andrew
Abstract : Background: HPV FOCAL, a large clinical trial conducted within an organized screening program setting, compared high-risk human papillomavirus (HPV) testing (Liquid based cytology (LBC) triage for HPV positives) to LBC for primary screening for cervical cancer. Primary endpoints included detection of high grade cervical intraepithelial neoplasia (CIN) grade 2 or greater (CIN2+) or grade 3 or greater (CIN3+) over 48 months in women 25–65 yrs of age. Methods: Over 18, 000 women were randomized into the HPV and LBC arms. HPV arm: baseline HPV testing; if HPV negative, exit at 48 months with HPV/LBC co-testing. LBC arm: baseline LBC testing; if LBC negative, screen at 24 months with LBC and exit at 48 months with HPV/LBC co-testing (in LBC arm, 48 months disease detection includes disease found at 24 months). We present 48 month exit CIN2+ results by age for baseline negative women. Results: At baseline, in the HPV arm, 8769 were HPV negative and in the cytology arm, 9074 were cytology negative. For all ages, at 48 months significantly more CIN2+ was detected in the LBC vs. HPV arm (10/1000 [95%CI: 8, 12] vs 4/1000 [95% CI: 3, 5], respectively, p<0.01). In both groups, CIN2+ exit screen detection rates were highest in the women 25–29 yrs of age at baseline screening (LBC 30.8/1, 000 & HPV 19.5/1, 000) and lowest in women 50+ at baseline (LBC 3.5/1, 000 & HPV 1.8/1, 000). Conclusion: At FOCAL exit where women were co-tested with LBC and HPV, less CIN2+ was detected across all age strata in women who were baseline HPV negative, than in baseline cytology negative women, confirming the safety of a 48 month interval for HPV negative women. In addition, the highest CIN2+ rates were detected in women who were 25–29 yrs at baseline and lowest in those 50+ at baseline, informing for age appropriate HPV-based program planning. Disclosure: No significant relationships.